Upholding the 4th estate—exploring the corporate governance of the media ownership form of business foundations. Issue 2 (3rd April 2018) - Achtenhagen, Leona; Melesko, Stefan; Ots, Mart
ABSTRACT: Whereas media ownership issues have interested scholars for decades, research has largely ignored the implications of specific ownership forms on the corporate governance of media companies, that is, how these companies are directed and controlled. This article attempts to address this gap by exploring the corporate governance of the ownership form of business foundations—a type of ownership that is increasing in different countries around the world. We analyze the corporate governance of three business foundations in the Swedish newspaper sector that together hold 26% of the market and outperform their industry peers. The control function, which is at the heart of corporate governance, is typically performed by companies' owners. However, foundations do not have a physical person as owner; thus, this control function is replaced by the foundation's charter, which stipulates the aim of the foundation's business activities. When steered by professional top management, the charter's long-term orientation facilitates the careful implementation of strategic directions without short-term performance pressures. We conclude the article by outlining several advantages and disadvantages of this ownership form for the media industry.